(untitled) (Academia Science Repository, 2023)
It is known that in the linguistics of the world, experiments were formed on the creation of compound words in the process of word formation, which is considered one of the aspects that clarify the wide internal possibilities of any language, on the comprehensive study of words belonging to this group at the grammatical level of the language, as well as on the use of research results in scientific directions. By comparing the formation methods of compound words with related Turkic languages, determining the objects of formation of compound words, studying the composition and types of compound words in historical and modern aspects are set as issues on the agenda. The historical-linguistic research of compound words is of particular importance in the special study of the Karakalpak language, in particular, the system of word formation.